Optimizing aerodynamic lenses for single-particle imaging. (October 2018) - Roth, Nils; Awel, Salah; Horke, Daniel A.; Küpper, Jochen
Abstract: A numerical simulation infrastructure capable of calculating the flow of gas and the trajectories of particles through an aerodynamic lens injector is presented. The simulations increase the fundamental understanding and predict optimized injection geometries and parameters. Our simulation results were compared to previous reports and also validated against experimental data for 500 nm polystyrene spheres from an aerosol-beam-characterization setup. The simulations yielded a detailed understanding of the radial phase-space distribution and highlighted weaknesses of current aerosol injectors for single-particle diffractive imaging. With the aid of these simulations we developed new experimental implementations to overcome current limitations. Abstract : Highlights: Demonstration of a new numerical particle trajectorie simulation infrastructure. Quantitative agreement of computations and experiments. Identification of weaknesses of currently used aerodynamic lens stacks. Proposal of optimized aerodynamic lens geometries. Sample density in SPI experiment is predicted to increase orders of magnitude.